2021
DOI: 10.1186/s13031-021-00366-5
|View full text |Cite
|
Sign up to set email alerts
|

Migrant children in transit: health profile and social needs of unaccompanied and accompanied children visiting the MSF clinic in Belgrade, Serbia

Abstract: Background Thousands of children migrate to Europe each year in search of safety and the promise of a better life. Many of them transited through Serbia in 2018. Children journey alone or along with their family members or caregivers. Accompanied migrant children (AMC) and particularly unaccompanied migrant children (UMC) have specific needs and experience difficulties in accessing services. Uncertainty about the journey and daily stressors affect their physical and mental health, making them o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Additionally, several other material factors limiting the efficacy of practice in the transit context, such as lack of funding and referrals for people in remote locations where support is not available, were considered important. This echoes findings from other researchers who have emphasized the need to increase accessibility to care in transit [ 47 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Additionally, several other material factors limiting the efficacy of practice in the transit context, such as lack of funding and referrals for people in remote locations where support is not available, were considered important. This echoes findings from other researchers who have emphasized the need to increase accessibility to care in transit [ 47 ].…”
Section: Discussionsupporting
confidence: 84%
“…The study revealed a need to define suitable MHPSS interventions for the transit context. There was support for developing a more flexible model of care ranging from community-based to specialized care, in accordance with past research on meeting mental health needs in the transit context [ 47 ]. This model should be adjusted to the needs of people on the move, which could be enabled by continuously assessing needs and by including refugees themselves in the design and provision of MHPSS services in the transit context.…”
Section: Discussionmentioning
confidence: 64%
“…It is also noted in literature that psychological distress among UACS was lower when they were placed in high support living arrangements in their resettlement (24). On the other hand, accompanied refugee children and youth, even when they are in an intact family, are influenced by family dynamics and their parents' mental health (8,23,25). We can summarize that proximity of parents, relatives and familiar adults is a strong risk or protective factor for children's mental health.…”
Section: Discussionmentioning
confidence: 55%
“…In a recent study also conducted in Serbia, similar findings were reported. The authors stated that UASC in Serbia most frequently reported that they suffered from anxiety, adjustment difficulties and PTSD, while accompanied youths surprisingly had slightly higher rates of depression and behavioral symptoms (23). However, it is important to emphasize that psychological distress of UASC depends on various factors that they are being exposed to during their transition and resettlement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation